1980
DOI: 10.1002/bjs.1800671005
|View full text |Cite
|
Sign up to set email alerts
|

Neural and humoral factors in postoperative ileus

Abstract: Two inhibitory mechanisms in the human colon which may contribute to postoperative ileus have been studied. Dopamine, a possible peripheral neurotransmitter, inhibited isolated colonic smooth muscle strips by a direct effect in longitudinal muscle any by a nerve-mediated mechanism as circular muscle. Plasma motilin levels were suppressed pre- and per- operatively and elevation of levels postoperatively correlated with the return of normal motility and the severity of the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…14) Clinically, it has been also reported that the blood motilin concentration is reduced in patients after laparotomy and postoperative ileus is improved as soon as the blood motilin concentration begins to recover from the early postoperative levels. 15,16) The amino acid sequence of human motilin remained unclear for a long time after the discovery of porcine motilin, but in 1987 was found to be identical to that of porcine motilin. 17) We thought that motilin may be useful for the treatment of gastroparalysis due to the pharmacological actions mentioned above.…”
mentioning
confidence: 99%
“…14) Clinically, it has been also reported that the blood motilin concentration is reduced in patients after laparotomy and postoperative ileus is improved as soon as the blood motilin concentration begins to recover from the early postoperative levels. 15,16) The amino acid sequence of human motilin remained unclear for a long time after the discovery of porcine motilin, but in 1987 was found to be identical to that of porcine motilin. 17) We thought that motilin may be useful for the treatment of gastroparalysis due to the pharmacological actions mentioned above.…”
mentioning
confidence: 99%
“…20,37,38 This was present at a range of frequencies, usually reported as 2-9 cpm, 9-14 cpm, and occasionally a high range of 20-28 cpm. 20,28,37,39 The dominant frequency identified varied by anatomical location; 2 studies reported 3 cpm activity in the sigmoid colon, 40,41 whereas other studies found that 9-14 cpm slow wave frequencies predominate in the right, transverse, and left colon during the first few days post-operatively. 20,28,37,38 Analyses of slow wave frequencies over time showed conflicting results.…”
Section: Transit Studiesmentioning
confidence: 99%
“…This might be responsible for the reduced duration and the retrograde migration of phase III of the MMC. The return of motilin to normal levels correlates with the resolution of ileus [50,51]. While sympathetic activation and the neurohumoral stress response have their onset immediately after surgery, inflammation of the gastrointestinal wall develops over several hours after the surgical intervention.…”
Section: Etiology Of "Normal" Postoperative Ileusmentioning
confidence: 99%